Urgency of implementing the OBE curriculum in BPI department based on user satisfaction - Ema Hidayanti; Maryatul Kibtyah; Namira Choirani Fajri; Triyana Febriyanti (Inovasi Kurikulum, 2025)
The high demand for high-quality higher education graduates encourages study programs to ensure that their curricula are on target. Therefore, curriculum development must involve graduate users so that the results can address problems and job market needs. This study aims to capture the satisfaction of graduate users of the Islamic Guidance and Counseling Study Program (BPI) at UIN Walisongo Semarang and to formulate the direction of curriculum development based on Outcome-Based Education (OBE), which focuses on da'wah competency. This study employs a qualitative method, collecting data through closed questionnaires, in-depth interviews, and discussion group forums with graduate users. The results of the study indicate that the portrait of graduate user satisfaction falls into the very good category, particularly in aspects such as ethics, cooperation, communication skills, and the use of information technology. Based on the results of the evaluation of graduate user satisfaction, the BPI Study Program formulated a Body of Knowledge (BoK) that makes da'wah the core of the OBE curriculum development. In this case, the four main disciplines that intersect with da'wah, namely, counseling, communication, guidance, and counseling, are the basis for the formation of the curriculum and courses. This study suggests that the OBE curriculum based on da'wah competency should continue to be improved so that it can meet the needs of the job market and be relevant in developing da'wah for the advancement of human civilization.   Abstrak Tingginya tuntutan kualitas lulusan pendidikan tinggi mendorong program studi untuk memastikan kurikulumnya tepat sasaran. Untuk itu, pengembangan kurikulum harus melibatkan pengguna lulusan sehingga hasilnya mampu menjawab permasalahan serta kebutuhan pasar kerja. Penelitian ini bertujuan untuk memotret kepuasan pengguna lulusan Program Studi Bimbingan dan Penyuluhan Islam (BPI) di UIN Walisongo Semarang serta untuk merumuskan arah pengembangan kurikulum berbasis Outcome-Based Education (OBE) yang berfokus pada kompetensi dakwah. Penelitian ini menggunakan metode kualitatif dengan pengumpulan data melalui angket tertutup, wawancara mendalam, dan forum grup disscussion dengan pengguna lulusan. Hasil penelitian menunjukkan bahwa potret kepuasan pengguna lulusan berada pada kategori sangat baik, terutama dalam aspek etika, kerja sama, kemampuan komunikasi, dan penggunaan teknologi informasi. Berdasarkan hasil evaluasi kepuasan pengguna lulusan tersebut, Program studi BPI merumuskan Body of knowledge (BoK) yang menjadikan dakwah sebagai inti dari pengembangan kurikulum OBE. Dalam hal ini, empat disiplin ilmu utama yang beririsan dengan dakwah, yaitu penyuluhan, komunikasi, konseling, dan bimbingan, menjadi dasar dalam pembentukan kurikulum dan mata kuliah. Penelitian ini menyarankan agar kurikulum OBE yang berbasis kompetensi dakwah terus disempurnakan agar dapat memenuhi kebutuhan pasar kerja dan relevan dalam pengembangan dakwah untuk kemajuan peradaban umat. Kata Kunci: body of knowledge; bimbingan dan penyuluhan Islam; kepuasan pengguna, kurikulum OBE; kompetensi dakwah